Uticaj poreskih podsticaja na rast poljoprivrednog izvoza sa dodatom vrednošću - dokazi iz Zimbabvea. - ABINAL, FORWARD; Mazuruse, Peter (Industrija, 2024)
This paper empirically examines the impact of export tax incentives on value-added agricultural export performance in Zimbabwe using historical annual time-series data from 1980-2021. The study uses unit root tests, cointegration analysis, and the Error Correction Model in the analysis. Using an augmented Cobb-Douglass production function, the study aims at determining wether export tax incentives, real effective exchange rate and value-added agricultural exports are cointegrated.. Export tax incentives and real effective exchange rate were found to have a positive and statistically significant effect in the long run on the country’s growth of value-added agricultural exports. From the results, policymakers are encouraged to deepen and broaden export tax incentives specifically targeted at value-addition of agricultural products as part of the country’s efforts in reforming its trade systemto improve the welfare of producers, workers and generate foreign currency for the country.